The procedural component of legal liability - L. I. Kalenichenko; D. V. Slynko (Bulletin of Kharkiv National University of Internal Affairs)
The procedural component of legal liability has been determined and analyzed. It has been proved that, first, legal liability arises only if there are necessary grounds, including the procedural basis; and secondly, the procedure for bringing to legal liability is determined by the norms of procedural law; thirdly, legal liability is implemented through the law-enforcement activities of the state.